Anti-VEGF drugs as the 2009 first-line therapy for choroidal neovascularization in pathologic myopia - Cohen, Salomon Y (Retina (Philadelphia, Pa.), 2009)
Pathologic myopia is the second cause of choroidal neovascularization, after age-related macular degeneration (AMD), and the first cause in patients younger than 50 years. The current treatment of subfoveal myopic choroidal neovascularization (mCNV) is verteporfin photodynamic therapy, but its long-term effectiveness has been disappointing. Antivascular endothelial growth factor (anti-VEGF) drugs are now widely used not only to treat choroidal neovascularization in AMD but also for choroidal neovascularization in other conditions. This review summarizes the data supplied by published case series studies about anti-VEGF therapy in mCNV. Analysis of the current literature allowed discussion of the optimal parameters for mCNV treatment by anti-VEGF, including the choice of anti-VEGF drug, its dose, the treatment protocol, and indications for retreatment. To date, the results of intravitreal bevacizumab or ranibizumab for mCNV have been reported in at least 14 studies, but they were all pilot, monocentric, and noncomparative case series. Nevertheless, they provided useful information on >250 patients and showed similar results, with significant improvement of visual acuity and an excellent safety profile. Shifting from one treatment to another is always difficult in the absence of prospective and controlled comparative studies. However, in 2009, intravitreal ranibizumab or bevacizumab may be considered as first-line therapy for sub- and juxtafoveal mCNV for three reasons: the safety of anti-VEGF drugs and intravitreal injection procedures; the disappointing long-term results of other therapies, including verteporfin treatment; and the excellent convergent results of anti-VEGF therapy in all pilot studies.